2015
DOI: 10.1371/journal.pcbi.1003883
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Modeling of Mouse Motor Activity under Deep Brain Stimulation: The Extraction of Arousal Information

Abstract: In the present paper, we quantify, with a rigorous approach, the nature of motor activity in response to Deep Brain Stimulation (DBS), in the mouse. DBS is currently being used in the treatment of a broad range of diseases, but its underlying principles are still unclear. Because mouse movement involves rapidly repeated starting and stopping, one must statistically verify that the movement at a given stimulation time was not just coincidental, endogenously-driven movement. Moreover, the amount of activity chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…As well as changes in plasma glucocorticoid levels, cardiovascular markers such as heart rate may provide useful markers of arousal. Furthermore, it has recently been suggested that spontaneous fluctuations in locomotor activity may provide a useful marker of generalized arousal ( 169 , 170 ), which may be beneficial for future studies in this field.…”
Section: Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…As well as changes in plasma glucocorticoid levels, cardiovascular markers such as heart rate may provide useful markers of arousal. Furthermore, it has recently been suggested that spontaneous fluctuations in locomotor activity may provide a useful marker of generalized arousal ( 169 , 170 ), which may be beneficial for future studies in this field.…”
Section: Cognitionmentioning
confidence: 99%
“…Inclusion of markers such as adrenal glucocorticoids provides one way of assessing arousal, though measurements of other parameters such as markers of cardiovascular function also be informative. Markers of generalized arousal, such as spontaneous fluctuations in locomotor activity may also be of value in this regard ( 169 , 170 ). While improved biomarkers of arousal are certainly needed, it should also be considered that arousal may not be a unitary process.…”
Section: Future Perspectivesmentioning
confidence: 99%